Benefits of once-daily therapies in the treatment of hypertension - Flack, John M (Dove Medical Press, 2011)
In patients with hypertension, 24-hour blood pressure control is the major therapeutic goal. The number of daily doses is one characteristic of an antihypertensive agent that may affect the adequacy of 24-hour control. One measure of therapeutic coverage is the 24-hour trough-to-peak ratio, which determines the suitability of an agent for once-daily administration. The closer an agent is to a 100% trough-to-peak ratio, the more uniform the 24-hour coverage and therefore blood pressure control. High trough-to-peak ratio, long-acting antihypertensive medications lower blood pressure more gradually, which reduces the likelihood of adverse events attributable to abrupt drug action that occurs with shorter-acting agents. In hypertension, the natural diurnal variation of blood pressure may be altered, including elevated nighttime pressures. An optimal once-daily hypertension therapy would not only lower blood pressure but also normalize any blunted circadian variations in blood pressure. The benefits of once-daily agents with sustained therapeutic coverage may also be explained, in part, by increased patient adherence to simpler regimens as well as lower loss of blood pressure control during virtually inevitable intermittent noncompliance. Studies have demonstrated that once-daily antihypertensive agents have the highest adherence compared with twice-daily or multiple daily doses, including greater adherence to the prescribed timing of doses.